Bibliometric Analysis of the Trend of Sociology of Communication Research Topics - Agustina Multi Purnomo (Ikatan Sarjana Komunikasi Indonesia, 2023)
Bibliometric analysis can provide extensive data mapping of previous research topic trends to formulate subsequent research topics. There is still a lack of bibliometric analysis of trends in sociology of communication research topics. The study used bibliometric analysis of 37,999 publications in ScienceDirect over three periods. Publication data was selected using the keyword